Influence of the mixture of Cd and BDE-209 on Zn and Cu homeostasis in rats - Ćurčić, Marijana; Janković, Saša; Buha Djordjević, Aleksandra; Milovanović, Vesna; Antonijević Miljaković, Evica; Djukić-Ćosić, Danijela; Javorac, Dragana; Baralić, Katarina; Živančević, Katarina; Božić, Dragica; Durgo, Ksenija; Vučinić, Slavica; et al. (Archives of Pharmacy, 2022)
Humans are exposed to the chemicals from very different sources. Therefore, the exposure assessment should be focused on mixtures rather than single chemicals. In this study, bioelements (Zn and Cu) homeostasis effects of mixture of Cd and BDE-209, widely spread persistent environmental pollutants, has been evaluated. In order to evaluate the potential of mixture on Zn and Cu homeosthasis in rats kidneys, Wistar rats were treated by oral gavage during 28 days with three doses of Cd 2.5, 7.5, and 15 mg/bw/day, three combinations of Cd with 1000 mg BDE-209/kg/day, and water as a control group. Kidney tissue samples were collected, mineralised, and Cu and Zn levels were measured by flame atomic absorbtion spectrophotometer. Possible interactions were evaluated comparing the dose-response curves slopes and lower confidence limit of Benchmark dose of 10% (BMDL10) were calculated by PROAST software (RIVM, Netherlands). Cd alone can disturb Zn in kidneys and calculated BMDL10 was 1.713 mg Cd/kg/day, while in combination with BDE-209 it was 1.719 mg/kg/day. Cd disturbs Cu in kidney in significantly higher dose of 5.679 mg Cd/kg/day. However, in combination with the BDE-209, derived BMDL10 was 10 times lower, 0.517 mg Cd/kg/day. Dose-response curve slope for the effect on Cu was significantly lower in the case of mixture effect than in the case of Cd effect. Since Cu plays a major role in the blood cells creation and health of other systems, our results indicate more potent activity of the mixture than single Cd.